Death and the Societies of Late Antiquity New methods, new questions? - Gaëlle, Granier; Boyer, Charlotte; Anstett, Élisabeth (Archéologies méditerranéennes, 2023)
This bilingual volume proposes to draw up an assessment of the recent research conducted on funerary behavior during Late Antiquity in the provinces of the Roman Empire and on their borders, in order to open new perspectives on its possible developments. The considerable transformations of the methodologies have raised the need for a renewal of the questions on the funerary practices during Late Antiquity, a period marked by multiple political, social, demographic and cultural changes. The emergence field anthropology, which was the beginning of archaeothanatology, and then the recent development of collaborative approaches between various scientific fields (archaeothanatology, biochemistry and geochemistry, genetics, history, epigraphy, for example), have been decisive. The research collected in this book is structured around four main themes: Evolution of funerary practices over time; Social identity through death; Changing burial grounds (organisation and topography); Territories of the Empire (from the heart to the margins). These studies propose a review and a revision of the data, both anthropological and archaeological or historical on Late Antiquity, and reveal a mosaic of political, social, and cultural landscapes singularly rich and complex. In doing so, they demonstrate that we can truly understand the cultural and social structures of ancient communities and their potential transformations, based on the study of funerary practices.